Coupled axial-shear numerical model for CLT connections. (30th September 2017) - Pozza, Luca; Saetta, Anna; Savoia, Marco; Talledo, Diego
Highlights: Proposal of new numerical model for CLT connections for coupled axial-shear actions. A specifically designed experimental campaign on hold-down connections is analyzed. The general model proposed is characterized to hold-down connections. Experimental and numerical results are compared for different lateral displacements. A CLT panel is modelled to investigate the influence of coupling effects. Abstract: A new coupled axial-shear numerical model is proposed to simulate the response of typical Cross Laminated Timber (CLT) connections under general loading conditions. The general model is then specialized for hold-down connections. To this aim, a series of experimental tests was first designed and performed at University of Bologna, in order to provide for the necessary data for the characterization of the numerical model. The main parameters required to define the constitutive law of the model are here evaluated by means of linear regression analyses performed on the experimental data. Both monotonic and cyclic test series are taken into account to calibrate and then validate the proposed numerical model, demonstrating its effectiveness in representing the coupled response of hold-down connections under simultaneous application of axial and shear forces. Finally, the response of a whole CLT panel subjected to a cyclic top displacement history is studied, confirming the need of considering axial-shear interaction in modelling of numerical connections.